Applications of Nanotechnology in Medicinal Chemistry Impact - M. Sarasija, (AG Volumes, 2025)
Nanomedicine is a broad use of nanotechnology in the medical domain. Particular nanoparticles may be used in imaging and methods, biomedical implants, targeted pharmaceutical products, tissue engineering, and novel diagnostic tools. An overview of the many studies on the use of nanotechnology in medicinal chemistry may be found in this article. According to the review, nanotechnology helps to maximise therapeutic efficacy, minimise the risk of adverse effects, and address the issue of focussed therapy delivery. This method is appropriate for cancer detection, treatment, and gene therapy. The realm of nanomedicine is where nanorobotics has the most potential for application. It is used in a wide range of sectors, including the creation of vaccines, medicine delivery, wearable technologies, diagnostic and imaging equipment, and antimicrobial products. Early illness detection, more powerful drugs, and improved equipment are expected to lead to nanomedicine. Combining conventional anti-cancer medications with nanoscale technology allows them to pass through intact and circulate throughout the brain. This technique provides whole classes of existing medications, as well as vast new markets and advantages.